Phenotypic insights into ADCY5‐associated disease. Issue 7 (8th April 2016) - Chang, Florence C.F.; Westenberger, Ana; Dale, Russell C.; Smith, Martin; Pall, Hardev S.; Perez‐Dueñas, Belen; Grattan‐Smith, Padraic; Ouvrier, Robert A.; Mahant, Neil; Hanna, Bernadette C.; Hunter, Matthew; Lawson, John A.; et al.
ABSTRACT: Background: Adenylyl cyclase 5 ( ADCY5 ) mutations is associated with heterogenous syndromes: familial dyskinesia and facial myokymia; paroxysmal chorea and dystonia; autosomal‐dominant chorea and dystonia; and benign hereditary chorea. We provide detailed clinical data on 7 patients from six new kindreds with mutations in the ADCY5 gene, in order to expand and define the phenotypic spectrum of ADCY5 mutations. Methods: In 5 of the 7 patients, followed over a period of 9 to 32 years, ADCY5 was sequenced by Sanger sequencing. The other 2 unrelated patients participated in studies for undiagnosed pediatric hyperkinetic movement disorders and underwent whole‐exome sequencing. Results: Five patients had the previously reported p.R418W ADCY5 mutation; we also identified two novel mutations at p.R418G and p.R418Q. All patients presented with motor milestone delay, infantile‐onset action‐induced generalized choreoathetosis, dystonia, or myoclonus, with episodic exacerbations during drowsiness being a characteristic feature. Axial hypotonia, impaired upward saccades, and intellectual disability were variable features. The p.R418G and p.R418Q mutation patients had a milder phenotype. Six of seven patients had mild functional gain with clonazepam or clobazam. One patient had bilateral globus pallidal DBS at the age of 33 with marked reduction in dyskinesia, which resulted in mild functional improvement. Conclusion: We further delineate the clinical features of ADCY5 gene mutations and illustrate its wide phenotypic expression. We describe mild improvement after treatment with clonazepam, clobazam, and bilateral pallidal DBS. ADCY5 ‐associated dyskinesia may be under‐recognized, and its diagnosis has important prognostic, genetic, and therapeutic implications. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society